Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1109/mcom.001.1900103
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Intelligent Edge: Wireless Communication Meets Machine Learning

Abstract: The recent revival of artificial intelligence (AI) is revolutionizing almost every branch of science and technology. Given the ubiquitous smart mobile gadgets and Internet of Things (IoT) devices, it is expected that a majority of intelligent applications will be deployed at the edge of wireless networks. This trend has generated strong interests in realizing an "intelligent edge" to support AI-enabled applications at various edge devices. Accordingly, a new research area, called edge learning, emerges, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
256
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 529 publications
(283 citation statements)
references
References 13 publications
0
256
0
1
Order By: Relevance
“…In contrast to the above research that has overlooked the participatory method to build a high-quality central ML model and its criticality, and primarily focused on the convergence of learning time with variants of learning algorithms, our work addresses the challenge in designing a communication and computational cost effective FL framework by exploring a crowdsourcing structure. In this regard, few recent studies have discussed about the participation to build a global ML model with FL as in [29], [30]. Basically, in [29] the authors proposed a novel distributed approach based on FL to learn the network-wide queue dynamics in vehicular networks for achieving ultra-reliable low-latency communication (URLLC) via a joint power and resource allocation problem.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the above research that has overlooked the participatory method to build a high-quality central ML model and its criticality, and primarily focused on the convergence of learning time with variants of learning algorithms, our work addresses the challenge in designing a communication and computational cost effective FL framework by exploring a crowdsourcing structure. In this regard, few recent studies have discussed about the participation to build a global ML model with FL as in [29], [30]. Basically, in [29] the authors proposed a novel distributed approach based on FL to learn the network-wide queue dynamics in vehicular networks for achieving ultra-reliable low-latency communication (URLLC) via a joint power and resource allocation problem.…”
Section: Related Workmentioning
confidence: 99%
“…The vehicles participate in FL to provide information related to sample events (i.e., queue lengths) to parameterize the distribution of extremes. In [30], the authors provided new design principles to characterize edge-learning and highlighted important research opportunities and applications with the new philosophy for wireless communication called learning-driven communication. The authors also presented some of the significant case studies and demonstrated the effectiveness of design principles in this regards.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [18], the authors developed a federated learning based spiking neural network. However, most of these existing works [7]- [18] whose goal is to minimize the FL convergence time must sacrifice the performance of the FL algorithm. For example, in [11] and [12], the authors sacrificed the training accuracy of FL to improve the convergence time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [11] and [12], the authors sacrificed the training accuracy of FL to improve the convergence time. Moreover, most of these existing works [7]- [18] used random or fixed user selection methods for FL training, which may significantly increase the FL convergence time and also decrease the FL performance. In addition, none of these existing works [7]- [18] considers the effect of the local FL models of the users that cannot connect to the BS due to limited wireless resource on the FL convergence time and performance.…”
Section: Introductionmentioning
confidence: 99%